Reversible watermarking in health data management - Bollineni, Sundeep (Kansas State University, 2010)
The area of health care delivery and medical data management has undergone a huge transformation in the recent years. This is directly related to the significant advancements in information and communication technologies. Vast amounts of medical data is to be efficiently stored, retrieved and distributed. The above mentioned reasons collectively have created new challenges, especially regarding the security of this highly sensitive information. Digital watermarking is a recently established area of research with many applications. The potential of medical image watermarking has only recently been realized by the research community. Medical image watermarking can be exploited to simultaneously address the issues of data security, archiving, retrieval and most importantly data authentication. This report discusses the perspectives of digital watermarking in the area of medical data management. Integer wavelet transform has been used to achieve reversible watermarking as every detail is important, especially in the case of medical images. Multiple watermarks which convey patient’s personal and examination data, keywords for information retrieval and the physician’s digital signature for authentication are embedded in an imperceptible manner. Different types of medical images have been acquired and tested using the proposed method.
Keywords: Watermarking; Medical; Engineering, Electronics and Electrical (0544)